2021
DOI: 10.1515/dmpt-2021-1000196
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of 95% khat ethanol extract (KEE) on human recombinant cytochrome P450 (CYP)1A2, CYP2A6, CYP2B6, CYP2C8, CYP2C19, CYP2E1, CYP2J2 and CYP3A5

Abstract: Objectives Khat, a natural amphetamine-like psychostimulant plant, are widely consumed globally. Concurrent intake of khat and xenobiotics may lead to herb-drug interactions and adverse drug reactions (ADRs). This study is a continuation of our previous study, targeted to evaluate the in vitro inhibitory effects of khat ethanol extract (KEE) on human cytochrome (CYP) 1A2, CYP2A6, CYP2B6, CYP2C8, CYP2C19, CYP2E1, CYP2J2, and CYP3A5, major human drug metabolizing enzymes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 65 publications
0
12
1
Order By: Relevance
“…25 Besides, the subsequent studies in our laboratory found that khat ethanol extracts inhibited most of the major drug metabolizing CYPs including CYP2A6, CYP2B6, CYP2C8, CYP2C19, CYP2E1, CYP2J2 and CYP3A5 except CYP1A2. 26 On the other hand, our ongoing investigations demonstrated that the CYPs were inhibited by cathinone differently from that of khat extracts (unpublished data). A study by Bedada et al 35 using human volunteers on one week of daily khat use (400 g) showed khat significantly inhibited CYP2D6, marginally inhibited CYP3A4, CYP2C19 and CYP1A2.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…25 Besides, the subsequent studies in our laboratory found that khat ethanol extracts inhibited most of the major drug metabolizing CYPs including CYP2A6, CYP2B6, CYP2C8, CYP2C19, CYP2E1, CYP2J2 and CYP3A5 except CYP1A2. 26 On the other hand, our ongoing investigations demonstrated that the CYPs were inhibited by cathinone differently from that of khat extracts (unpublished data). A study by Bedada et al 35 using human volunteers on one week of daily khat use (400 g) showed khat significantly inhibited CYP2D6, marginally inhibited CYP3A4, CYP2C19 and CYP1A2.…”
Section: Discussionmentioning
confidence: 96%
“…59 The current study utilizes high-throughput fluorescencebased assays for detection of enzyme-drug interactions. 26,60 In spite of that, a number of caveats exist in this in vitro study using recombinant enzyme preparations as compared to human liver microsomes or hepatocytes. In real-life, owing to the different non-specific binding, accessory proteins or proteinprotein interactions, the enzyme matrix itself may contribute to prominent variations in IC 50 values from one in vitro system to the other 61 which could not be investigated using the current in vitro methods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations